THE NEEDS ANALYSIS OF FOUR PRIMARY LANGUAGE SKILLS IN DEVELOPING JAPANESE TEACHING MATERIALS FOR TOURISM PURPOSES - Juangsih, Juju; Emzir, Emzir; Rasyid, Yumna (Jurnal Pendidikan Bahasa dan Sastra, 2020)
The aim of this study was to analyse the needs of four primary language skills in developing Japanese teaching materials for tourism purposes. Research data was collected by applying questionnaire and interview method. In Tourism and Marketing Management Study Program - FPIPS UPI, the needs analysis result of Japanese teaching materials for tourism showed the average level of percentage ranging from 4 to 5 by applying Likert scale measurement. Based on the questionnaire conducted to 40 participants, speaking skills showed the highest response rate, both from students and lecturer’s perception. Listening Skills from student’s perception yielded approximately 86% or an average of 4.3, while from lecturer’s perception yielded 90% or an average of 4.5. Meanwhile, speaking skills from student’s perception reach 95% response rate or an average of 4.7, and from lecturer’s perception yielded 100% response rate or an average of 5.0. For the need of reading skills, student’s perception showed 86% response rate or an average of 4.3, and 80% or an average of 4.0 for lecturer’s perception. Further, the need of writing skills yielded 88% or an average 4.4 response rate from the students’ perception, and 80% or an average of 4.0 response rate of the lecturer’s perception.